Effectiveness of E-mail Support to Increase Physical Activity Within the Workplace - Woolmer, Jillian; Howat, Peter; Sauer, Kay (2005)
A brief intervention was conducted to assess the effectiveness of a walking based intervention to motivate Curtin university staff to be more active. Thirty staff participated in a blind trial with half the participants randomly allocated to the control group (given pedometers to record their normal daily steps) and intervention group (given pedometers and additional email motivation to increase their daily step count).It was found that University staff physical activity levels (7,605 mean steps per day) were significantly lower than physical activity levels of the general population in Western Australia (9,695 mean steps per day). This is of concern as it places University staff at higher risk of mortality and morbidity from chronic diseases.Regular motivational emails were found to be useful in encouraging staff to be more active as staff liked the social support, sense of belonging and encouragement. Group 1 (email motivation) increased their mean steps significantly from 7,578 in Week 1 to 9,128 in Week 2 while the control group did not change.Many workplaces have staff with sedentary jobs that could be targeted by similar flexible physical activity interventions.